A Comprehensive Review of Utility-Scale Battery Energy Storage: Technologies, Control Strategies, Planning Methods, and Future Directions - Deliu, Andrei-Darius; Cazacu, Emil (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Variable renewable energy from wind and photovoltaics is expanding rapidly, increasing net-load ramps, curtailment risks, and voltage–frequency excursions that stress conventional operating practices. Utility-scale battery energy storage offers fast active-power response and independent P–Q control, enabling frequency regulation, voltage support, ramp control, and multi-hour energy shifting while coordinating with plant and system controls. This review synthesizes the current state of technology and practice for large-scale storage in wind and PV integration. We examine architectures and components from battery chemistry to power-conversion systems, supervisory control, thermal and safety design, and AC versus DC coupling within hybrid plants [1]. We survey control strategies spanning grid-following and grid-forming operation, including droop and virtual-inertia behaviors, and relate these to operational roles in transmission, distribution, and microgrids. Planning methods are organized around siting, sizing, and dispatch optimization with explicit treatment of degradation and techno-economic outcomes. Evidence from studies and deployments is consolidated to quantify impacts on stability, reliability, hosting capacity, and non-wires deferral. The review concludes with priorities for research and deployment, including scalable grid-forming validation, health-aware dispatch and markets, and pathways that combine lithium-ion with longer-duration storage where adequacy and flexibility needs converge. [2],[5],[3]